The Role of the Central and Kuibyshev Institutes of Maternal and Child Welfare in the Creation of Maternal and Child Health Care Service in the USSR (1922-1940) - R. S. Serebryany; S. A. Sher; O. V. Yaremchuk ("Paediatrician" Publishers LLC, 2016)
The article focuses on the role of the State Research Institute of Maternal and Child Welfare as the lead establishment and of the Kuibyshev Regional Scientific-Practical Institute of Maternal and Child Welfare in the creation of maternal and child health care service in the Soviet Union during 1922-1940. It also presents the scientific-practical, educational, organizational-methodological activities of the central and peripheral institutions, their comparative characteristics and contribution to the creation of a broad network of institutions for maternal and child welfare (nurseries, maternity welfare centres, baby food centers, social-legal offices) and the reduction of morbidity and mortality of infants and young children.